Identification and prevalence of gastro-intestinal parasites among students aged 4-6 in two schools in Brgy.183, Pasay City. - Cacabilos, Evena Flor L. 4 0 16; 5
u
Thesis:(B.S. Biology)- Pamantasan ng lungsod ng Maynila.
Keywords: 2 -- 0; 6; 20; 20; 2